Sistem informasi kepegawaian untuk perusahaan pembangkit listrik menggunakan model Rapid Application Development - Wegie, Sabrina; Darmawan, Fitrah Asma (Universitas Merdeka Malang, 2023)
The employee information system is an important tool for companies to manage employee data to make it easier, safer and more accurate. PT PLN Nusantara Power UP PLTU Tanjung Awar-Awar is a power plant unit under PT PLN which has approximately 700 employees consisting of pure employees from PT PLN and outsourced employees. However, currently the Human Resources division does not have the means to manage existing personnel administration. This causes the data not to be captured digitally so the data search process takes a long time. In this research, a website-based personnel information system was developed to handle personnel master data. The software development method used is the RAD (Rapid Application Development) model. This method is expected to save time in development. The program functionality testing method uses blackbox testing, and USE questionnaires as user satisfaction tests. In testing this application, 6 respondents were used who were company administration staff. The results obtained were that an employee information system was produced with a functionality category suitable for acceptance. Usability testing obtained a result of 79.44%, namely the category suitable for use.